2003
DOI: 10.1177/089686080302300204
|View full text |Cite
|
Sign up to set email alerts
|

Association between an Increased Surface Area of Peritoneal Microvessels and a High Peritoneal Solute Transport Rate

Abstract: Objective The peritoneal solute transport rate (PSTR) often increases, especially for small solutes, during long-term peritoneal dialysis (PD) treatment. Although the mechanism by which PSTR increases in PD patients is not known, it is likely that an increased PSTR reflects an increased surface area of the peritoneal capillary and postcapillary venules (microvessels), but this has not previously been investigated. The aim of this study was to clarify the relationship between PSTR and peritoneal microvessel alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 14 publications
0
49
1
Order By: Relevance
“…Although the mechanism by which PSTR increases in PD patients is not fully understood, angiogenesis might have an important role. Numata et al (7) reported that the peritoneal microvessels area was positively correlated with the D/P Cr obtained by a PET.…”
Section: Discussionmentioning
confidence: 96%
“…Although the mechanism by which PSTR increases in PD patients is not fully understood, angiogenesis might have an important role. Numata et al (7) reported that the peritoneal microvessels area was positively correlated with the D/P Cr obtained by a PET.…”
Section: Discussionmentioning
confidence: 96%
“…In the sections stained against CD31, we estimated the twodimensional "microvessel density"; that is, the total number of cross sections of CD31+ microvessels per area of submesothelial compact connective tissue (microvessel profiles/mm 2 ) (21). This parameter is analogous to the "relative microvessel number" used by Numata et al (7) or the "microvessel density" used by Sherif et al (3). It was calculated as the number of microvessel profiles per reference area in five image fields sampled from the submesothelial compact zone in a systematic uniform random manner (using a ¥20 objective).…”
Section: Methodsmentioning
confidence: 99%
“…Hirahara et al (14)(15)(16) focused on the fact that MMP-2 increased in the effluent in the experimental model of sclerosing peritonitis (SP)/ encapsulating peritoneal sclerosis (EPS) in rats and reported that MMP-2 can be a good marker for diagnosing SP/EPS. Numata et al (17) reported that an increased peritoneal solute transport rate (for both creatinine and b2MG) is associated with an increased surface area of peritoneal microvessels. Our results suggest that the increases in multiple peritoneal injury factors owing to ICO dwell, such as proinflammatory cytokines, angiogenic factors, and matrix metalloproteinases, might enlarge the surface area of peritoneal microvessels.…”
Section: S Minami Et Al 298mentioning
confidence: 99%